RUANG DAN KULTUR KEKERASAN DOMESTIK: PENGALAMAN PEREMPUAN MADURA DI KEMAYORAN BARU SURABAYA - . Sarmini (Humaniora, 2008)
This study is aimed to comprehensively understand the cultural reproduction of gender violence such as how it happens and what implications it gives to the lives of women; how it is understood and manifested, and; what factors contribute to the violation. Phenomenology by focusing heavily on observation during the field reasearch. The study was conducted in the Madurese community in Kemayoran Baru, Kelurahan Krembangan Selatan, Kecamatan Krembangan, Surabaya Municipality. In the community, violence is perceived to have very noble goals. Violence has social logic and is related to different orientations of life and to expectations to be achieved. Women’s attitude to give in to men was the manifestation of an attempt to reach a noble expectation of building and maintaining a harmonious family. Violence is perceived as part of a normal system of family and considered to be equivalent to the prevailing norms and values. Families have both shared values and conflicting values in social interaction and exchange. Therefore, violence against women should not be observed partially, separately, and independently of the prevailing social activities. To wisely identify the essence of violence, violence should be understood holistically in relation to the constructions of different reasons and motives which contribute to the occurrence of violence.